influence of hepatitis B DNA level and antiviral therapy on recurrence after initial curative treatment in patients with hepatocellular carcinoma - Chuma, Makoto; Hige, Shuhei; Kamiyama, Toshiya; Meguro, Takashi; Nagasaka, Atsushi; Nakanishi, Kazuaki; Yamamoto, Yoshiya; Nakanishi, Mitsuru; Kohara, Toshihisa; Sho, Takuya; Yamamoto, Keiko; Horimoto, Hiromasa; et al. (Journal of gastroenterology, 2009)
Background Prediction and prevention of hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC) recurrence is an important clinical issue. We investigated whether HBV DNA level and antiviral therapy are associated with HCC recurrence. Methods This retrospective study involved 103 patients who underwent hepatic resection or radiofrequency ablation for initial HCC. Patients were divided into four groups. Thirty had high serum HBV DNA levels (>4 log₁₀ copies/mL) and had not received antiviral therapy (high virus group; HVG). Thirty-four had low HBV DNA levels (<=4 log₁₀ copies/mL) and had not received antiviral therapy (low virus group; LVG). Twenty received antiviral therapy after HCC developed (therapeutic group A, TG-A). Nineteen received antiviral therapy before HCC developed (therapeutic group B, TG-B). Results Cumulative HCC recurrence rates at 3 years in the HVG, LVG, TG-B, and TG-A were 71.1%, 42.2%, 42.3%, and 52.0%, respectively. Recurrence rates differed significantly between the HVG and LVG (P = 0.016) and between the HVG and TG-B (P = 0.008). Recurrence rate in the TG-A was marginally lower than in the HVG (P = 0.10). On multivariate analysis, high serum hepatitis B virus DNA levels (hazard ratio: HR 2.67; 95% CI 1.31-5.47; P = 0.007) and absence of antiviral therapy (HR 2.57; 95% CI 1.34-4.94; P = 0.005) were independent risk factors for hepatocellular carcinoma recurrence. Conclusion HBV DNA level and antiviral therapy are associated with HCC recurrence. For patients with high HBV DNA levels, antiviral therapy before the development of HCC is important for prevention of recurrence.